Divergent - Roth, Veronica, (HarperCollins Publishers, 2011)
In sixteen-year-old Beatrice Priors world, society is divided into five factions -Abnegation-the selfless, Candor -the honest, Dauntless-the brave, Amity-the peaceful, and Erudite-the intelligent -each dedicated to the cultivation of a particular virtue, in the attempt to form a perfect society. In a future Chicago, sixteen-year-old Beatrice Prior must choose among five predetermined factions to define her identity for the rest of her life, a decision made more difficult when she discovers that she is an anomoly who does not fit into any one group, and that the society she lives in is not perfect after all